Imaging Recommendations for Diagnosis, Staging, and Management of Bladder and Urethral Malignancies - Majithia, Jinita; Prakash, Gagan; Thakur, MH; Popat, Palak; Sable, Nilesh; Katdare, Aparna; Kulkarni, Suyash; Chandra, Daksh (Indian Journal of Medical and Paediatric Oncology, 2023)
Bladder cancer (BCa) is a leading cause of cancer worldwide with high incidence and mortality across all ages. Early diagnosis and treatment can lead to significantly improved survival rate and overall prognosis. Smoking is the biggest contributing factor for the development of BCa. Urothelial carcinoma is the most common histological subtype. Commonly implemented imaging techniques include computed tomography urography (CTU) and multiparametric magnetic resonance imaging (mpMRI). CTU is the investigation of choice for muscle invasive bladder cancer (MIBC) and is best utilized for local assessment and staging of larger and higher staged tumors, that is, T3b and T4. mpMRI encompasses T2-weighted imaging, diffusion-weighted imaging, and dynamic contrast-enhanced imaging. It can differentiate ≤T1 and ≥T2 tumors based on the Vesicle Imaging-Reporting and Data System (VI-RADS) assessment as well as differentiate Ta from T1 tumors, and is useful in post-therapy response assessment of BCa. Positron emission tomography/computed tomography is used in selected patients of MIBC for metastatic evaluation, particularly those with deranged renal function. A synoptic reporting template should be used to have standardization of data. Primary urethral cancer (UCa) is a rare and aggressive malignancy, accounting for less than 1% of all malignancies. MRI is the investigation of choice for UCa.
Keywords: bladder cancer; radiology; staging; urethral cancer; urology